The Role of LP3H in Increasing the economic Value through Assistance with Halal Certification - Hidayati, Lutfi; Sugiatmi, Sugiatmi; Aini, Nur; Yulika Go, Ratna (Indonesian Journal of Islamic Economics and Business, 2023)
Indonesian government is targeting one million halal product certification in 2023. And the government is targeting that by 2024 all products in Indonesia will be halal certified. This certainly needs support from various parties. Indonesian government through the Halal Product Assurance Organizing Agency (BPJPH) appoints the Halal Product Process Assistance Agency (LP3H) which acts as an extension and assists business actors (micro - small) through assistance in the halal certification process. However, data on the halal information system shows that only 749,971 products have been declared halal in 2022 and there is still a need for massive socialization efforts so that government programs are realized. To support this program, LP3H ITB AD conducts activities for prospective Halal Product Process (PPH) assistants to help verify and validate the halal process for business actors. The aim of the research is to disseminate basic information and knowledge to prospective PPH assistants regarding the legal basis, verification, validation, materials and processes for halal certification. The method used in this research is descriptive quantitative. Data collection was obtained from the results of the questionnaire. The results of this study show that on average 66% of the participants understand the information material related to the halal process and 79% are very satisfied with the presentation of the resource persons.